Program Edukasi Trading Dasar melalui Sosialisasi dan Simulasi Trading Menggunakan Akun Demo - Hapsari, Dinda Dewi; Santoso, Bowo (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The development of financial technology has made investment activities, including trading, more accessible to the public. However, many university students are interested in engaging in trading without sufficient understanding of its fundamental principles and associated risks. To address this issue, a basic trading education program was implemented through socialization activities and demo account simulations, allowing participants to practice directly without financial risk. The materials provided covered an introduction to financial markets, trading platform mechanisms, and virtual transaction exercises. Evaluation results indicate an improvement in participants’ knowledge related to risk concepts, basic analysis, and market operations. This program is expected to enhance students’ financial literacy and encourage wiser decision-making in trading and other investment activities.